Вихрострумовий дефектоскоп з телеметричним каналом зв'язку - Протасов, А. Г.; Сєрий, К. М.; Дугін, О. Л.; Петрик, В. Ф. (НТУ "ХПІ", 2014)
В роботі запропоновано схему дефектоскоп для вихрострумового неруйнівного контролю, який має телеметричний канал зв'язку з пристроєм обробки і відображення інформації. Створений дефектоскоп має малу вагу і розміри, що дозволяє використовувати його для контролю складних конструкцій. Телеметричний канал зв'язку здійснює обмін даними за рахунок бездротової технології Bluetooth, що дає можливість залучати для обробки цих даних потужну обчислювану техніку.

It is proposed the diagram of an eddy current defectoscope for nondestructive testing which has telemetric connection with the information processing and view device. The introduced defectoscope has possibility to connect some of transducers or defectoscopes to a singular view device (computer). The telemetric channel uses Bluetooth wireless technology and can provide communication in two directions for large quantity of parameters. They are oscillograms, a received signal’s amplitude and phase, a frequency and amplitude of the excitation signal, an operation threshold of the audio alarm and others. The defectoscope engineering solution gives resources to adjust features of the measuring instrument during operating modes and automation of testing processes with following data storage in the computer memory. The created defectoscope has small size and weight. It can be used for testing of the complex construction. The telemetric communication channel makes it possible for using high-powered computer to signal processing. The results of experimental investigation confirm of possibility to test metallic samples by proposed defectoscope.
The eddy current defectoscope with telemetric communications channel
Keywords: вихрострумовий дефектоскоп; телеметричний канал зв'язку; контроль виробів; системи неруйнівного контролю; бездротові технології передачі даних; eddy current defectoscope; telemetric communications channel